Enzymatic Production of Rare Sugars with a New Mutant of Cellobiose 2-Epimerase from Caldicellulosiruptor Saccharolyticus - Vera-Vera, C (Elsevier Ltd, 2024)
Cellobiose 2-epimerase from Caldicellulosiruptor saccharolyticus (CsCE) can epimerize and isomerize lactose into epilactose and lactulose respectively. Competition between these reactions reactions has prompted the search for new enzymes to drive the reaction in one direction or the other. The isomerization and epimerization capacity of a novel mutant CsCE (CsCE H356N) was evaluated, obtaining a maximum lactulose yield of 64.3 % and a lactulose selectivity of 9.9. A Michaelis-Menten constant of 551.93 mM and a catalytic efficiency of 0,058 s−1 mM−1 were obtained for lactose epimerization. The ability of CsCE H356N to recognize other substrates was evaluated using lactulose, glucose, mannose, fructose, galactose, talose and tagatose as substrates, assessing the reversibility of such reactions. Yields of 14.8 % mannose and 4.8 % of fructose were obtained from glucose, while talose and tagatose yields of 9.2 % and 5.2 % were obtained from galactose respectively. No significant reaction occurred with lactulose, fructose or tagatose as substrates. © 2023 Elsevier Ltd